2008
DOI: 10.2753/ced1061-1932410506
|View full text |Cite
|
Sign up to set email alerts
|

Left-Behind Children in Rural Primary Schools: The Case of Sichuan Province

Abstract: During China's economic transformation, much of the rural population migrated to urban areas in search of employment opportunities. "Left-behind children" are the product of this phenomenon and need significant attention. Our study adopted elementary school students in Sichuan province as the subjects. After carefully studying their academic conditions, we discovered that the "left-behind" experience has negative effects on these children's schoolwork. Children who have had both parents or the mother leave nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…It has been found that the academic standing of children left behind is worse than children who live with their parents, and this is especially the case for children's confidence and interest in learning (Liang, Hou, and Chen 2008). Many children left behind report a need for tutoring support (Xu 2009).…”
Section: The Needs Of Children Left Behind In Rural Chinamentioning
confidence: 96%
“…It has been found that the academic standing of children left behind is worse than children who live with their parents, and this is especially the case for children's confidence and interest in learning (Liang, Hou, and Chen 2008). Many children left behind report a need for tutoring support (Xu 2009).…”
Section: The Needs Of Children Left Behind In Rural Chinamentioning
confidence: 96%
“…To be more exact, the lack of family education and generation-skipping education render poor academic conditions for the group (e.g., Li, 2015;Wang & Wang 2005;Wang & Wu 2003;Pan & Ye, 2017). Liang, Hou, and Chen (2008) describe a more in-depth investigation of the schoolwork of left-behind children. This can be based on data from a large-scale sampling survey with multivariate regression models from students' grades, gender, family factors, and school characteristics.…”
Section: Journal Of Studies In Social Sciences 220mentioning
confidence: 99%
“…Co-ordination and Control of Funds. First of all, scientific research and personnel advantages of universities' own should be used, by the increasing cooperation with local and enterprises, to transfer patent technology, provide paid services, carry out different ways of joint of school and government, joint of enterprise and school, joint among schools, and attract capital investment, equipment investment or various forms of resources on the university's investment, in order to maximize the increase in funding sources [5,6]. Second, the funds of university and other resources should be concentrated to a large financial system, the allocation of funds are changed from the original way, which distributes by the department and the special objects, to the way, which distributes only by special allocation and set aside a certain amount of mobility funds.…”
Section: Solutionsmentioning
confidence: 99%